Online homework system for mathematics form three - Siti Aisyah Ramle; Noor Anida Zaria Mohd Noor (Journal of ICT in Education, 2022)
Homework plays a vital role in learning experiences, especially in Mathematics subject. However, when an unexpected global emergency happens (COVID’19 Pandemic), the schools close, and students face difficulties with their studies as many schools still use classic style homework, which is paper-based homework. The problem arises when educators or teachers do not have the appropriate medium or platform to communicate and provide learning materials to their students. Thus, Online Homework System for Mathematics Form Three is an alternative learning medium for secondary school students to solve this problem. This web-based system is able to assist teachers in uploading homework for students. Students can also access the system to download their homework regardless of the places within the internet coverage without relying solely on the printed version. This system is developed based on the ADDIE model and the evaluation is conducted through questionnaires instruments, which involved 35 respondents from form three students and two mathematics teachers. Evaluation is to test the usability and effectiveness of the system. The findings indicate this system is easy to use, makes the learning process easier, provides the expected function, and is needed nowadays.